2016
DOI: 10.1371/journal.pone.0164078
|View full text |Cite
|
Sign up to set email alerts
|

Ossicular Bone Damage and Hearing Loss in Rheumatoid Arthritis: A Correlated Functional and High Resolution Morphometric Study in Collagen-Induced Arthritic Mice

Abstract: Globally, a body of comparative case-control studies suggests that rheumatoid arthritis (RA) patients are more prone to developing hearing loss (HL). However, experimental evidence that supports this hypothesis is still lacking because the human auditory organ is not readily accessible. The aim of this study was to determine the association between bone damage to the ossicles of the middle ear and HL, using a widely accepted murine model of collagen-induced arthritis (RA mice). Diarthrodial joints in the middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Mixed HL with normal tympanic membrane is classically associated with otosclerosis or third window lesions like semicircular canal dehiscence or enlarged vestibular aqueduct (with pseudo-conductive HL). Another hypothesis would be rheumatoid arthritis as these lesions were described in murine model histopathology (5). Here, imaging ruled out these differential diagnoses and clinical and biological results were not consistent with rheumatoid arthritis.…”
Section: Imaging Findingsmentioning
confidence: 80%
“…Mixed HL with normal tympanic membrane is classically associated with otosclerosis or third window lesions like semicircular canal dehiscence or enlarged vestibular aqueduct (with pseudo-conductive HL). Another hypothesis would be rheumatoid arthritis as these lesions were described in murine model histopathology (5). Here, imaging ruled out these differential diagnoses and clinical and biological results were not consistent with rheumatoid arthritis.…”
Section: Imaging Findingsmentioning
confidence: 80%
“…Diarthrodial type incudostapedial and inkudomalleolar joints in the middle ear can be affected by RA. [3] While the ankylosis in the joints leads to a decrease in ossicular movements, more importantly its piston effect does not change. It has been reported that SNHL is more common in RA patients (24-60%) and it is caused by RA influencing the inner ear.…”
Section: Resultsmentioning
confidence: 99%
“…Although hearing impairment occurs frequently in patients with autoimmune disease, the pathogenesis of hearing impairment remains controversial [ 13 , 15 ]. Bone defects in the middle ear were observed in murine models of RA and destruction of the incudostapedial and incudomalleolar joints can result in impaired conduction [ 18 , 34 ]. However, it does not necessarily lead to a hearing impairment [ 6 , 17 , 23 ].…”
Section: Discussionmentioning
confidence: 99%